Islam’s position on treaties - عبدالله ظاهر محسن (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
The Arabs before Islam knew treaties and alliances, due to differences and aggression against each other, which prompted them to ally and conclude treaties with their neighboring tribes or tribes that impede their movement and trade, as well as gaining strength and victory from others when they engage in a specific battle or respond to an attack on their tribe from their neighbors or From others, so we find that this tribe has allied itself with another tribe for the purpose of gaining supremacy and control over the closest tribes close to it, and this situation includes almost most of the Arab and non-Arab tribes, and the situation has changed after the emergence of Islam in the Arabian Peninsula, so loyalty to religious belief became first and last, Commitment to fulfilling promises, alliances and treaties, and not treachery and betrayal, and this is indicated by the texts of the Noble Qur’an and the narrations issued by the Messenger of God, may God’s prayers be upon him and his family, and the infallible imams, peace be upon them. This is a study on the position of Islam on concluding treaties and the necessity of fulfilling them. This study was divided into the following demands: The first requirement: the definition of treaties in language and terminology. The second requirement: Treaties among the pre-Islamic Arabs. The third requirement: the treaties of Islam and the obligation to fulfill them. The fourth requirement: types of treaties in Islamic law. The fifth requirement: the treaties of the Prophet (PBUH) with the infidels and the People of the Book. The sixth requirement: Treaties of Muslims with others after the death of the Prophet (PBUH). Then I finished with the results of the research and a conclusion, and praise be to the Lord of the Worlds.